Le copertine di Pitigrilli. Un fenomeno editoriale tra testo e paratesto - Bonciarelli, Sarah (Incontri. Rivista europea di studi italiani, 2012)
The book covers of Pitigrilli. An editorial phenomenon between text and paratext The subject of the article is the analysis of the literary case of Pitigrilli, one of the most important authors of the middlebrow literature in Italy between the two world wars. Pitigrilli is particularly interesting for his capacity to represent the apparent contrast between a popular and broadly diffused literature and a quality literary product. His work also shows the contaminations between the popular literature and the artistic avant-gardes, between the advertising world and the world of literature, between textual and iconic aspects. Thanks to Pitigrilli the popular novel acquired a specific standing, kicking off a process of demolition of the rigid borders between the high standing culture and the popular culture, between the élite culture and the mass culture. The objective of this article is to analyze a particular aspect of the literary case of Pitigrilli: the covers of the novels where the images are integrated with the use of language, in order to give to the final readers some additional instruments to have access to the text.